nth term in a binomial expansion (a+b)^n is given by
T(r+1) = nCr*a^(n-r)*b^r
= 22Cr*(3)^(22-r)*(x)^(22-r)*(-1)^r*(1/x^2)^r
Collect the terms containing x and simplify. Equate the power of x to 4 and find the value of r.
So I'm doing find the coefficient of x^4 in (3x-(1/x^2))^22
I've done where a = 3x and b = 1/x^2
(22)
(K) (3x)^K (-1/x^2)^(22-K)
(22)
(K) (3^K) (x^K) (-1)^(22-K) x^-2(22-K) ----- I think this is where I've stuffed up
(22)
(K) (3^K) (-1)^(22-K).... not sure from here lol.
Please help! Would be appreciated.